THE IMPORTANCE OF MOTIVATION IN LEARNING ENGLISH. (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
Students' motivation is very important in language learning. It is important to encourage EFL (English as a Foreign Language) students to participate in the learning process. According to Dornyei (1998), motivation is responsible for determining human activity by energizing and directing it. Motivating students can give them a way to achieve their goals. One of the main aspects of a person is communication. According to Lewis (Lewis, Simons, & Fennig, 2014), English is the third most spoken language in the world. Therefore, English is very important to communicate with people around the world. According to Gardner (1985), which has been recognized for a long time, it is recognized that one of the main elements influencing the learning of English language is the learner's motivation.